2013
DOI: 10.1007/s00406-013-0404-5
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime cannabis use and cognition in patients with schizophrenia spectrum disorders and their unaffected siblings

Abstract: The relationship between cannabis and cognitive performance is controversial. While both acute administration and long-term cannabis use impair cognitive performance in healthy subjects, several studies have shown improved cognitive outcomes in patients with schizophrenia spectrum disorders who use cannabis. The aim of this study was to determine the relationship between lifetime cannabis use, as assessed longitudinally over 10 years of follow-up in a sample of 42 patients and 35 of their unaffected siblings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 49 publications
0
14
0
7
Order By: Relevance
“…The findings are not inconsistent with the experimental data; it is likely that persons who smoke cannabis have higher premorbid IQ, as evidenced by their ability to procure an illegal substance while evading the law. Therefore, although continued cannabis use results in a decline in their individual cognitive performance (242, 248, 249), when compared to non-users they appear to have relatively better cognitive performance. Furthermore, abstinence from cannabis may be associated with better cognitive performance among male patients with schizophrenia (248).…”
Section: Delayed and Persistent Effects Of Cannabinoidsmentioning
confidence: 98%
“…The findings are not inconsistent with the experimental data; it is likely that persons who smoke cannabis have higher premorbid IQ, as evidenced by their ability to procure an illegal substance while evading the law. Therefore, although continued cannabis use results in a decline in their individual cognitive performance (242, 248, 249), when compared to non-users they appear to have relatively better cognitive performance. Furthermore, abstinence from cannabis may be associated with better cognitive performance among male patients with schizophrenia (248).…”
Section: Delayed and Persistent Effects Of Cannabinoidsmentioning
confidence: 98%
“…Cognitive alteration in patients with schizophrenia can be associated with cannabis use , negative and schizotypy symptoms and medical comorbidities such as diabetes mellitus, hypertension, dyslipidemia, and obesity . Other influencing factors include decreased gray matter density in the cerebellum , reduced blood omega‐3 fatty acids , N‐methyl‐d‐Aspartate receptor (NMDAR) hypofunction and inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Weibell et al found that patients who had quit cannabis use in the first two years of the disease had similar outcomes at 10‐year follow‐up to those who had never used cannabis and fewer symptoms than persistent or sporadic users who presented more severe negative symptomatology and lower remission rates. In terms of cognitive functioning, in the 10‐year follow‐up study of Sanchez‐Torres et al , no significant correlations were found between the lifetime cannabis consumption and cognitive performance in their sample of patients affected by schizophrenia spectrum disorders.…”
Section: Introductionmentioning
confidence: 84%